Semantic similarity estimation of tasks between telecommunications business processes (2012)
As a measure to improve competitiveness in the telecommunications market, companies in the sector currently create new value-added services, in order to expand their portfolio of services and ensure either the permanence of their customers or expand the number of subscribers . These new services must be supported in the business processes defined by the Telecommunications Operator, which are composed of operation, management, maintenance and support tasks. Telco Architects usually reuse these tasks with the objective of optimizing the company's resources and guaranteeing the rapid recovery of the investment, amortizing in the shortest possible time the creation and deployment costs of the new service.